2022
DOI: 10.3389/fnmol.2022.984655
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane phospholipid phosphatase-related proteins as pleiotropic regulators of neuron growth and excitability

Abstract: Plasma membrane phospholipid phosphatase-related proteins as pleiotropic regulators of neuron growth and excitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 154 publications
0
7
0
Order By: Relevance
“…The intracellular region of PLPPR3, as well as other PLPPRs, likely mediates the filopodia formation function as well as protein-protein interactions. [1][2][3][9][10][11][12] However, the regulation of PLPPR3 by post-translational modifications is currently not understood. We tested the presence of phosphorylation, the most pervasive and well-understood post-translational modification, in primary cortical neurons at DIV9, when PLPPR3 expression peaks in culture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The intracellular region of PLPPR3, as well as other PLPPRs, likely mediates the filopodia formation function as well as protein-protein interactions. [1][2][3][9][10][11][12] However, the regulation of PLPPR3 by post-translational modifications is currently not understood. We tested the presence of phosphorylation, the most pervasive and well-understood post-translational modification, in primary cortical neurons at DIV9, when PLPPR3 expression peaks in culture.…”
Section: Resultsmentioning
confidence: 99%
“…PLPPR3 phospho-mutants showed equivalent plasma membrane localization with the WT protein, which is considered a requisite of PLPPR-induced filopodia formation. 1 However, there were no differences in filopodia density between the phosphomutants and the WT (Figure 3H, I). Thus, we concluded that phosphorylation of PLPPR3 S351 does not regulate filopodia formation.…”
Section: Plppr3 S351 Is a Pka Phosphorylation Sitementioning
confidence: 89%
See 2 more Smart Citations
“…PRG3 and PRG5 belong to the family of plasticity-related genes (PRGs), which defines a subclass of the Lipid Phosphate Phosphatase (LPP) superfamily. The PRG family comprises five, vertebrate, brain-specific membrane proteins, which influence lipid phosphate signaling and thereby promote filopodia formation, neurite extension, axonal sprouting and reorganization after lesions [ 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Although PRG3 and PRG5 share the highest structural and sequence similarities within the PRG family, their short (~50 amino acids) intracellularly located C-termini are unique [ 16 , 18 ], which indicates that they might exert different functions in cells compared to each other.…”
Section: Introductionmentioning
confidence: 99%